Novel molecular prognostic and diagnostic techniques in colorectal cancer - Somayeh Igder; Mozhdeh Zamani; Shima Fakher; Morvarid Siri; Hassan Ashktorab; Hassan Brim; Marek J. Łos; Pooneh Mokarram (Iranian Journal of Colorectal Research, 2022)
Background Colorectal cancer (CRC) is one of the more diffuse reasons for malignancy-associated death worldwide. According to the evidence that CRC is predominantly symptomless as it advances to the highest stages, the administration of screening schemes planned at initial diagnosis is required to lower the prevalence and fatality rate . We aimed to review the literature on different molecular procedures for detection of stool-based biomarkers in CRC. Methods and Evidence Acquisition In the current study we reviewed papers of Google Scholar and PubMed database with no time limitation. Conclusion An integrative framework of all epigenetic and genetic modifications compared to other traditional procedures were studied which represented a more acceptable specificity and sensitivity for the diagnosis, treatment, evaluating drug response and also the clinical outcome of CRC. Differential expression analysis of stool-derived RNAs (sRNAs) and stool DNA (sDNA) testing for ultrasensitive mutations, methylation, and fragmentation patterns can lead to an early-stage diagnosis and a better prognosis for CRC patients in a higher accuracy.